RRerum Novarum di Era Digital: Tantangan dan Peluang Baru Dunia Kerja (International Forum of Researchers and Lecturers, 2024)
The digital era brings fundamental transformation to the world of work, requiring a critical review through the perspective of the Church's social teachings, particularly the Rerum Novarum Encyclical. This research aims to analyze the challenges and opportunities of the labor world amid the digital revolution using the ethical framework of this historic document. The study employs a descriptive quantitative approach. The analytical methods include literature review, interpretation of secondary data on digital transformation, and comparative evaluation between the principles of Rerum Novarum and contemporary employment conditions. The article reveals that digital transformation is not just about technological advancement, but also about ensuring human welfare. The ethical approach inherited from Rerum Novarum can serve as a guide in designing inclusive and just employment policies. To face the digital era, a comprehensive strategy is needed that integrates technological innovation with worker rights protection. Digital literacy, equitable technology access, and social protection policies become key elements in achieving a dignified transformation.